Importers, exporters, and exchange rate disconnect - Mary Amiti; Oleg Itskhoki; Jozef Konings (National Bank of Belgium, 2012)
Large exporters are simultaneously large importers. In this paper, we show that this pattern is key to understanding low aggregate exchange rate pass-through as well as the variation in pass-through across exporters. First, we develop a theoretical framework that combines variable markups due to strategic complementarities and endogenous choice to import intermediate inputs. The model predicts that firms with high import shares and high market shares have low exchange rate pass-through. Second, we test and quantify the theoretical mechanisms using Belgian firm-product-level data with information on exports by destination and imports by source country. We confirm that import intensity and market share are the prime determinants of pass-through in the cross-section of firms. A small exporter with no imported inputs has a nearly complete pass-through of over 90 %, while a firm at the 95th percentile of both import intensity and market share distributions has a pass-through of 56 %, with the marginal cost and markup channels playing roughly equal roles. The largest exporters are simultaneously high-market-share and high-import-intensity firms, which helps explain the low aggregate pass-through and exchange rate disconnect observed in the data.
Keywords: F14; F31; F41; 330; Exchange rate pass-through; pricing-to-market; import intensity; Exchange Rate Pass-Through; Außenhandelssektor; Import; Großunternehmen; Marktanteil; Exportwirtschaft; Belgien